Measles infection in lady Ridgeway hospital in 2013: a case control study - Navageevan, N.; Punchihewa, P.M.G.; Kumarendran, B.; Hathagoda, K.L.W.; Galappaththi, A.G.A.R.; Jayathilaka, A. (Sri Lanka College of Paediatricians, 2015)
BACKGROUND:A measles outbreak was reported in 2013 in the Lady Ridgeway Hospital for Children (LRH).OBJECTIVES:To describe the epidemiology of measles among paediatric patients admitted to LRH. DESIGN, SETTING AND METHOD:This case control study, conducted among patients admitted to LRH, recruited 167 clinical cases and 693 controls of six to 24 months age. All the clinically positive cases admitted to any of the six paediatric medical units during January to June 2013 and four patients admitted following each case were included. Data was gathered from the bed head tickets using data extraction sheet and by telephone interview. Significance was assessed at 5% level.RESULTS:Of the 140 clinical cases with available reports, 126 (90%) were positive for measles lgM (confirmed cases - CC). The CC included 75 (60%) males, 48 (38%) aged up to 9 months and 50 (40%) aged 10 to 12 months. Clinical features among the CC include high fever (100%), rash (100%), cough (94%), coryza (83%), conjunctivitis (63%), Koplik spots (14%), post measles staining (31%), diarrhoea (48%) and vomiting (31%). Complications among the CC included at least one complication (68%), pneumonia (65%) and 2 cases of death. Of the 47 CC with positive contact history, 41 had contacts in the hospital. Of the 28 cases aged above 12 months, 23 did not receive measles vaccine.Measles status was associated with measles vaccination status among children above 12 months of age (P<0.001), contact history (P<0.001), ethnicity (P<0.001) and mother's education (P<0.01). There was no evidence for an association of measles infection status with sex (p=0.9), income (p=0.3) and weight for age (p=0.2). CONCLUSIONS: • Around 78% cases were below 12 month old. • Majority of cases above 12 month of age did not receive measles vaccine. • Majority of cases had contact history in the hospital.
Free Papers Abstract (FP24), 18th Annual Scientific Sessions, Sri Lanka College of Paediatricians, 30th July to -2nd August 2015 Colombo, Sri Lanka
Keywords: Measles infection